Frequency and Distribution of Diagnoses of Functional Occlusal Disorders among Patients Treated at the Teaching Dental Clinic of the Peruvian Cayetano Heredia University - Paz Mayurí, Carlos Alberto (2023)
Objective:The objective of the present study was to determine the frequency and distribution of diagnoses of functional occlusal disorders among patients treated in undergraduate and postgraduate oral rehabilitation at the Teaching Dental Clinic of the Peruvian Cayetano Heredia University between 2016 and 2017. Material andmethods:The research was descriptive, retrospective, observational, and cross-sectional. The variables considered were the diagnoses of functional occlusal disorders, classifying them by gender, age, educational level, and location. A database comprising all digitized medical records was used with a case presentation planned and accepted by the tutoring teacher and a certificate of commitment accepted by the patient. Results: It was found that the most common diagnosis was collapsed occlusion (38.69% of diagnoses, n = 166), followed by occlusal disharmony (36.13%, n = 155), posterior bite collapse (10.72%, n = 46), upper and lower total edentulous (7.69%, n = 33),traumatic occlusion (5.83%, n = 25), and the combination syndrome (0.93%, n = 4). Conclusions: Most of the patients analyzed (n = 429) were women. The average age was 56.79 years, with most patients analyzed aged between 60 and 69. Undergraduate students made the highest number of diagnoses. Most diagnoses were made at the San Martín de Porres center.